Contribución al bienestar y buen vivir, por medio de un artefacto para el entrenamiento recreativo de artes marciales mixtas (MMA) (2019)
The objective of the work was to design an artifact for the training of MMA through positive design, proposing innovation strategies that promote the well-being of users. It is an excellent tool which allows getting involved with psychological, physical and emotional aspects of the human being as a way of contributing to positive emotions to improve the quality of life, well-being and good living of young novice mixed martial artists from the city of Bogotá, Colombia that oscillate in ages from 17 to 23 years